2018
DOI: 10.1111/jgh.14293
|View full text |Cite
|
Sign up to set email alerts
|

State of the art review with literature summary on gastric peroral endoscopic pyloromyotomy for gastroparesis

Abstract: Gastroparesis is a debilitating progressive disease that significantly impacts a patient's life with limited and challenging treatments available. Although the pathogenesis is multifactorial, pylorospasm is believed to have a major underlying role. Several therapeutic interventions directed to the pylorus have been developed over the last decade, including intra-pyloric injections of botulinum toxin, transpyloric stenting, and surgical pyloroplasty. All of these treatment options had limited and disappointing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Endoflip technology might be a tool for the selection of appropriate patients in the future, but more research is needed. Short-term clinical success at 3 months (defined as a significant improvement in GCSI) has been reported in 73 % -90 % of patients with refractory gastroparesis undergoing G-POEM [150]. Long-term data are missing and the recurrence rate is not known.…”
Section: Gastric Peroral Endoscopic Myotomy (G-poem)mentioning
confidence: 99%
“…Endoflip technology might be a tool for the selection of appropriate patients in the future, but more research is needed. Short-term clinical success at 3 months (defined as a significant improvement in GCSI) has been reported in 73 % -90 % of patients with refractory gastroparesis undergoing G-POEM [150]. Long-term data are missing and the recurrence rate is not known.…”
Section: Gastric Peroral Endoscopic Myotomy (G-poem)mentioning
confidence: 99%
“…Gastric per oral endoscopic myotomy (G-POEM) is an endoscopic technique in which a longitudinal incision is created in the circular smooth muscle of the pylorus, typically between 1.5-2 cm. 53 G-POEM is the latest evolution in interventional procedures which target pylorospasm. Prior to G-POEM, the more invasive surgical pyloroplasty has been shown to improve symptoms and gastric emptying in gastroparesis and underpins the theoretical basis of G-POEM.…”
Section: Gastric Per Oral Endoscopic Myotomymentioning
confidence: 99%
“…Given its value and clinical success, variations of POEM are emerging and have shown promise in endoscopic management of similar difficult conditions including refractory gastroparesis, oesophageal and Zenker's diverticulum, and reflux post-POEM. In a review of seven studies on G-POEM, Khoury et al 39 have reported technical success in 100% of cases, clinical efficacy in 81.5% and normalisation of measures in gastric emptying studies in 55.5% of cases, with complications between 6.6% and 7.6%. The findings support its efficacy and use in the treatment of gastroparesis after failure of conventional therapy.…”
Section: Poem Subtypesmentioning
confidence: 99%